Assessment of #TheDress With Traditional Color Vision Tests: Perception Differences Are Associated With Blueness. (March 2018) - Feitosa-Santana, Claudia; Lutze, Margaret; Barrionuevo, Pablo A.; Cao, Dingcai
Based on known color vision theories, there is no complete explanation for the perceptual dichotomy of #TheDress in which most people see either white-and-gold (WG) or blue-and-black (BK). We determined whether some standard color vision tests (i.e., color naming, color matching, anomaloscope settings, unique white settings, and color preferences), as well as chronotypes, could provide information on the color perceptions of #TheDress. Fifty-two young observers were tested. Fifteen of the observers (29%) reported the colors as BK, 21 (40%) as WG, and 16 (31%) reported a different combination of colors. Observers who perceived WG required significantly more blue in their unique white settings than those who perceived BK. The BK, blue-and-gold, and WG observer groups had significantly different color preferences for the light cyan chip. Moreland equation anomaloscope matching showed a significant difference between WG and BK observers. In addition, #TheDress color perception categories, color preference outcomes, and unique white settings had a common association. For both the bright and dark regions of #TheDress, the color matching chromaticities formed a continuum, approximately following the daylight chromaticity locus. Color matching to the bright region of #TheDress showed two nearly distinct clusters (WG vs. BK) along the daylight chromaticity locus and there was a clear cutoff for reporting WG versus BK. All results showing a significant difference involved blue percepts, possibly due to interpretations of the illuminant interactions with the dress material. This suggests that variations in attributing blueness to the #TheDress image may be significant variables determining color perception of #TheDress.